2020
DOI: 10.1371/journal.pone.0240697
|View full text |Cite
|
Sign up to set email alerts
|

The impact of brain iron accumulation on cognition: A systematic review

Abstract: Iron is involved in many processes in the brain including, myelin generation, mitochondrial function, synthesis of ATP and DNA and the cycling of neurotransmitters. Disruption of normal iron homeostasis can result in iron accumulation in the brain, which in turn can partake in interactions which amplify oxidative damage. The development of MRI techniques for quantifying brain iron has allowed for the characterisation of the impact that brain iron has on cognition and neurodegeneration. This review uses a syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 89 publications
1
31
1
Order By: Relevance
“…The study by Gao et al also showed that serum iron concentrations were only positively correlated with brain iron in the right hippocampus and were not correlated with brain iron other regions of interest [ 37 ]. A recent review summarized that iron accumulated heterogeneously across brain regions, and Caudate nuclei, Hippocampus and Thalamus were the regions where iron was most frequently reported to correlate with memory performance, while iron deposition in the putamen was correlate to poorer general cognition [ 7 ]. These findings suggested that abnormal iron status might have different effects on various brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Gao et al also showed that serum iron concentrations were only positively correlated with brain iron in the right hippocampus and were not correlated with brain iron other regions of interest [ 37 ]. A recent review summarized that iron accumulated heterogeneously across brain regions, and Caudate nuclei, Hippocampus and Thalamus were the regions where iron was most frequently reported to correlate with memory performance, while iron deposition in the putamen was correlate to poorer general cognition [ 7 ]. These findings suggested that abnormal iron status might have different effects on various brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…A further aim of the present study was to investigate the relationships between brain iron, cognition and motor function, with the hypothesis that such relationships may differ according to HFE genotype. Based on growing evidence that higher iron load is generally deleterious to cognitive performance in older adults 6,27 and that C282Y/H63D is associated with disturbed iron metabolism leading to iron overload, the expectation that higher iron in the HFE ‐pos group would be related to lower performance was reasonable. On the other hand, the limited literature on this topic has provided mixed findings, with some beneficial effects observed in HFE ‐pos individuals.…”
Section: Discussionmentioning
confidence: 99%
“…For the analyses, we focused on the basal ganglia (caudate, putamen, pallidum) because iron accumulates most in these regions, and they are relevant for cognitive performance 2,6,27 . In addition, we added an average measure of cortical iron, which includes all cortical regions of the cerebrum as segmented by Freesurfer, from which we excluded the medial temporal lobe, where artifacts were detected notably in the parahippocampal gyrus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A hallmark of senescent or dystrophic microglia in the ageing brain is the accumulation of iron [ 55 , 167 , 168 , 169 ], with documented negative impacts on cognition. The accumulation of iron is noted in regions that are particularly vulnerable to pathology in Parkinson’s Disease (PD) [ 170 ], with iron loaded, dystrophic microglia being found associated with Lewy Bodies.…”
Section: Microglia In Neurodegenerationmentioning
confidence: 99%